Notice of the Early Ecclesiastical Settlements at St Andrews - Skene, William F (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author attempts to identify when the veneration of St Andrews began in Scotland. This under-researched period of Scottish history is mentioned in several Saints’ Lives and legends, which Skene compares to the recorded royal and ecclesiastical history of the Picts. He concludes by arguing that the church was first founded in 736 by members of the exiled Northumbrian clergy.